Modulação centro-contorno em campos receptivos do wulst visual - Ana Luiza Turchetti Maia (2011)
Neurons in the primary visual cortex (V1) typically show responsesuppression when stimulated by oriented stimuli larger than their classical receptive fields (CRF). Here, we investigate the prevalence, strength and feature selectivity of center-surround modulation in the owl visual wulst, an area that presents close hodological and physiological similarities to V1. In total, we recorded 167 neurons using standard single-unit extracellular recordings in awake burrowing owls, Athene cunicularia. Our dataset consisted of units that presented evoked activity larger than baseline and were significantly modulated by stimulus size. In a subset of neurons (n=145), we evaluated the response to drifting sinusoidal grating of increasing size centered in the middle of CRF fittedwith a difference of two integrated Gaussians, one modeling excitatory center mechanisms and the other one modeling inhibitory surround. Among well-fitted units (n=144), 88% of visual wulst neurons were suppressed by co-stimulating center and surround areas. The magnitude of this suppression was widely distributed (median=33%) and correlated to the ratio between center (median=2.17º, n=114) and surround sizes (median=7.84º, n=86). In most cells, the suppressive effect appeared already at the start of the response, up to 30ms after response latency. When stimulating with a surround patch of grating, 74% out of 38 units showed response levels similar to baseline. The remainingunits reached this level only when the inner border of the surround patch was moved away from the CRF border. As we introduced a 0.9º gap between center and surround (n=28), absence of response change was observed in 78.6% and 57.2% of units when center and surround gratings were collinear and orthogonal, respectively. Stimulus contrast variation (10% and 97%, n=33) showed that CRF size in these neurons is not invariant, as it is slightly larger at low contrast in 88% of units. Besides, in 67% of neurons, suppression index was larger for higher contrast, showing a tendency to be less suppressed for larger receptive field sizes. We did not find facilitatory effects when surround was orthogonal to center. Mean CRF size, as well as suppression index, was statistically not different between simple and complex cells. However, in a subset of neurons with suppression > 5% (n=66), 80.3% of the evaluated cells presented an increase in phase-modulation depth of the response as stimulus size was increased. We conclude that center-surround modulation in visual wulst neurons is a robust phenomenon, probably related to perceptual saliency.